2013
DOI: 10.1364/oe.21.025271
|View full text |Cite
|
Sign up to set email alerts
|

Localized enhancement of electric field in tip-enhanced Raman spectroscopy using radially and linearly polarized light

Abstract: Finite-Difference Time-Domain (FDTD) calculations are used to characterize the electric field in the vicinity of a sharp silver or gold cone with an apex diameter of 10 nm. The simulations are utilized to predict the intensity and the distribution of the locally enhanced electric field in tip-enhanced Raman spectroscopy (TERS). A side-by-side comparison of the enhanced electric field induced by a radially and a linearly polarized light in both gap-mode and conventional TERS setup is performed. For this purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 27 publications
1
65
1
Order By: Relevance
“…Our study offers the opportunity to improve the preparation of TERS tips by a systematic comparison between the intensity of the TERS signal and the tip optical response. Several numerical simulations have already demonstrated the best configuration to achieve high electromagnetic enhancements . The role of polarization, tip‐to‐surface distance, excitation wavelength, and so forth, is clearly evidenced in these studies.…”
Section: Introductionmentioning
confidence: 70%
“…Our study offers the opportunity to improve the preparation of TERS tips by a systematic comparison between the intensity of the TERS signal and the tip optical response. Several numerical simulations have already demonstrated the best configuration to achieve high electromagnetic enhancements . The role of polarization, tip‐to‐surface distance, excitation wavelength, and so forth, is clearly evidenced in these studies.…”
Section: Introductionmentioning
confidence: 70%
“…On the other hand, the calculated electric field in the gap between the particles shows large changes with polarization, see Figure 2, consistent with previous studies. 51, 54 …”
Section: Resultsmentioning
confidence: 99%
“…5 exemplifies the field distribution for two configurations: with a 10 nm gold layer and without a metal substrate [82]. Fig.…”
Section: Polarization Controlmentioning
confidence: 99%
“…The enhancement factor goes from 8 to 10 for linearly polarized along the tip axis, and 82 to 322 for linearly polarized perpendicular to tip axis and from 720 to 11510 for radially polarized light. It has been shown that objects that are sandwiched between the tip and flat gold surfaces would show high local Raman signal enhancement [82,83].…”
Section: Polarization Controlmentioning
confidence: 99%